2007
DOI: 10.1097/01.olq.0000218880.88179.36
|View full text |Cite
|
Sign up to set email alerts
|

High Uptake of Postpartum Hormonal Contraception Among HIV-1-Seropositive Women in Kenya

Abstract: Using existing the healthcare infrastructure, it is possible to achieve high levels of postpartum hormonal contraceptive utilization among HIV-1-seropositive women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 13 publications
2
30
0
Order By: Relevance
“…In particular, and in contrast with our hypothesis, women receiving HAART were significantly more likely to report contraceptive use while HIV-positive HAART-naïve women were non-significantly more likely to use contraception compared with HIV-negative women. Overall, over 80% of HIV-positive women in our study reported contraceptive use, which falls within the upper range reported for HIV-positive women elsewhere in sub-Saharan Africa (46%–85%) [16], [17], [25], [32], [42], [43]. Contraceptive prevalence among HIV-negative women in our study was 69%, which is highly comparable to estimates among women in the general South African population [41].…”
Section: Discussionsupporting
confidence: 79%
“…In particular, and in contrast with our hypothesis, women receiving HAART were significantly more likely to report contraceptive use while HIV-positive HAART-naïve women were non-significantly more likely to use contraception compared with HIV-negative women. Overall, over 80% of HIV-positive women in our study reported contraceptive use, which falls within the upper range reported for HIV-positive women elsewhere in sub-Saharan Africa (46%–85%) [16], [17], [25], [32], [42], [43]. Contraceptive prevalence among HIV-negative women in our study was 69%, which is highly comparable to estimates among women in the general South African population [41].…”
Section: Discussionsupporting
confidence: 79%
“…Taking HIV prevention a step further to include access to effective family planning services for women living with HIV who want to avoid an unplanned pregnancy [37] can prevent more paediatric HIV infections than is promised by the current low coverage of prevention of mother-tochild transmission programmes.…”
Section: Gender and Hiv Preventionmentioning
confidence: 99%
“…75 More research is needed regarding access to and use of contraceptive methods among HIV positive women and men, in order for services to be better able to tailor service delivery to them. 76 …”
Section: Service Delivery Implicationsmentioning
confidence: 99%
“…The small proportion of women who develop heavy bleeding with either method need to be treated promptly to avoid serious consequences. 76,89 Research is needed on interactions between medical abortion drugs and antiretroviral therapies, as evidence is scarce. Improvements in provider-patient relations should contribute to a better understanding of and response to factors that can affect health care needs of women living with HIV, 90 as well as to adequate postabortion family planning counselling.…”
Section: Service Delivery Implicationsmentioning
confidence: 99%